(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
The research aimed to monitor and analyze the press coverage of crime in the Syrian daily journalism, in terms of the extent of the press attention, the types of topics and issues addressed, and styles and trends addressed. The research depended on analysing the content in Al-Watan & Al-Thawra Newspapers during the first half of 2019, by following industrial week method, where drawn sample reached to 48 numbers in rate, and the number of articles that were subjected to analysis reached (85) articles from Al-Thawra newspaper, and (93) articles from Al-Watan newspaper. Research Results showed the two newspapers’ interest in covering corruption issues in the first place, while the type of press coverage of crime varied, as Al-Thawra newspaper focused on news coverage, and adopted the method of storytelling without mentioning causes and solutions, which is consistent with its use of the news in most of its articles, while Al-Watan newspaper focused on documentary coverage, and mentioned the reasons which is consistent with its use of the reports in the first place. The results showed the commitment of the two newspapers to ethical principles, as each of them worked to present several aspects of the event, follow neutrality due to the lack of opinion materials, and attribute information to its sources. The research called for the need to pay attention to covering all types of crimes, and not only to report facts, but to go beyond this role to awareness and guidance by providing Explanative materials in addition to Informative materials, and to employ journalistic types such as features and interviews, wich is more appropriate to crime cases and have the ability to provide causes and solutions or treating and raising awareness about crimes, especially local ones, in light of their increasing rate during the Syrian crisis.